2012
DOI: 10.1007/s00227-012-1940-7
|View full text |Cite
|
Sign up to set email alerts
|

Food sources used by sediment meiofauna in an intertidal Zostera noltii seagrass bed: a seasonal stable isotope study

Abstract: In an intertidal Zostera noltii Hornem. seagrass bed, food sources used by sediment meiofauna were determined seasonally by comparing stable isotope signatures (δ 13 C, δ 15 N) of sources with those of nematodes and copepods. Proportions of different carbon sources used by consumers were estimated using the SIAR mixing model on δ 13 C values. Contrary to δ 15 N values, food source mean δ 13 C values encompassed a large range, from-22.1‰ (suspended particulate organic matter) to-10.0‰ (Z. noltii roots). δ 13 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 63 publications
3
46
0
Order By: Relevance
“…This is in accordance with the diet of copepods in P. oceanica meadow sediments (Danovaro et al, 2002), Zostera noltii meadow sediments (Lebreton et al, 2012;Vafeiadou et al, 2014), and in salt marshes (Couch, 1989), or in Amphibolis sp. and Posidonia spp.…”
Section: Discussionsupporting
confidence: 87%
“…This is in accordance with the diet of copepods in P. oceanica meadow sediments (Danovaro et al, 2002), Zostera noltii meadow sediments (Lebreton et al, 2012;Vafeiadou et al, 2014), and in salt marshes (Couch, 1989), or in Amphibolis sp. and Posidonia spp.…”
Section: Discussionsupporting
confidence: 87%
“…Olsen et al () reported that benthic invertebrates feed on seagrass in estuaries where the seagrass biomass is large relative to that of macroalgae. Additionally, Lebreton et al () reported a similar availability of seagrass as a diet resource for nematodes living several centimeters below the sediment surface. The consumption of seagrass‐derived organic matter by bacteria in surface sediments has also been suggested (Williams et al ).…”
Section: Discussionmentioning
confidence: 98%
“…Less information is available for meiobenthos resource utilization in seagrass beds (Vizzini et al, 2000b(Vizzini et al, , 2002aBaeta et al, 2009;Leduc et al, 2009;Lebreton et al, 2011Lebreton et al, , 2012, with none of the studies including meiofauna at the level of feeding types, families, genera or species. The few studies using natural isotope abundances to unravel food resources of coastal meiofauna at this level (Carman and Fry, 2002;Moens et al, , 2005Moens et al, , 2013Rzeznik-Orignac et al, 2008) do not examine seagrass habitats.…”
Section: Introductionmentioning
confidence: 99%